Pengaruh Murottal Al-Qur’an terhadap Daya Ingat Mahasiswa Universitas Muhammadiyah Surakarta - Asyifa Azdkiah Haqiqi; Nihayatun Naja; Ayu Dwi Lestari Putri; Aisyah Elsa Setyadi; Siti Rafifah Qonitah Aminuddin; Ricki Bayu Saputra; Alifa Choirun Nisa (PSIKOLOGI KONSELING, 2025)
This study aims to analyze the effect of Qur’anic murottal on memory performance among students of Universitas Muhammadiyah Surakarta. The research employed an experimental method using a post-test control group design. The sample consisted of 30 students randomly divided into experimental and control groups. The instrument used was the Merkaufgaben (ME) subtest from the Intelligenz Struktur Test (IST). Mann-Whitney test results showed a significance value of 0.041 (≤ 0.05), indicating that the hypothesis is accepted. The findings suggest that listening to Qur’anic murottal has a positive impact on students’ memory performance.